ChemInform Abstract: A DFT Based Prediction of Gold Fullerene Au92Si12 with the Aid of Silicon. Issue 35 (2nd September 2014) - Gautam, Seema; Goel, Neetu; Dharamvir, Keya
Abstract The structure, stability, and effect of doping Aun (n = 1—16) clusters with Si is investigated by DFT calculations.